Automation of Cyber Attack Mitigation on RouterOS Using n8n Orchestration Platform - Arief Budi Pratomo (Bulletin of Network Engineer and Informatics, 2026)
The security of network infrastructure using MikroTik RouterOS is frequently compromised by automated cyber attacks, such as brute force and port scanning, which require rapid mitigation to prevent unauthorized access. This research aims to develop an automated mitigation system by utilizing n8n as a low-code workflow orchestrator to enhance response efficiency. The research method involves integrating RouterOS syslogs with n8n via a webhook or database trigger, which then automatically executes blocking commands through the MikroTik API when a threat is detected. The results demonstrate that the system can identify and isolate malicious IP addresses within seconds, significantly reducing the window of vulnerability compared to manual administrative intervention. In conclusion, the implementation of n8n provides an effective and scalable solution for real-time cyber attack mitigation, ensuring better network stability and security.